(untitled) (Journal of Laboratory Animal Science, 2021)
Laboratory mice constitute the most popular animal models used in biomedical research today. Like all animals, even mice housed in ‘barrier’ facilities are prone to infection. Wild mice (Mus musculus) living near vivaria could serve as a source of infection or infestation in laboratory mouse colonies, although little is known about the prevalence of infectious diseases in wild mouse. Very few surveys have been conducted on wild rodent populations to determine the prevalence of viruses and bacteria and also health monitoring of the wild rodents. Pathogens (bacteria, parasites) often gain entry into colonies through the introduction of infected animals or infected animal products, but viral dissemination via contaminated fomites or local wild rodents has also been implicated in the spread of disease. Hence, a preliminary study was undertaken to determine the prevalence of rodent pathogens and health status in wild mouse populations in and around and Bangalore. The present study revealed that none of the animals tested were positive for viral pathogens. However, bacterial pathogens and parasites were found in wild caught mice. Hematological and serum biochemical parameters were comparable to the colony bred anim